2012
DOI: 10.4012/dmj.2012-019
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of direct inlay-retained adhesive bridges: Effect of pontic material and occlusal morphology

Abstract: This study evaluated the effect of a) pontic materials and b) occlusal morphologies on the fracture resistance of fi ber-reinforced composite (FRC) inlay-retained fi xed dental prostheses (FDP). Inlay-retained FRC FPDs (N=45, n=9) were constructed using a) resin composite (deep anatomy), b) natural tooth, c) acrylic denture tooth, d) porcelain denture tooth and e) resin composite (shallow anatomy), as pontic materials. In addition resin composite beams were fabricated (N=30, n=10): i) 'circular', ii) 'elliptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Since, these applications are metalfree, minimal invasive, cost-effective, tissue-saving and aesthetic; they might be used in patients for replacing missing single or multiple anterior or posterior teeth 3,4) . Previous in vitro and in vivo studies are available in literature regarding load-bearing capacities of inlayretained FRC fixed-dental-prosthesis (FDPs) [5][6][7] . A previous study evaluated the effect of pontic materials and occlusal morphologies on the fracture resistance of FRC inlay-retained FDPs and reported that load-bearing capacity values were between 509-598 N 5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, these applications are metalfree, minimal invasive, cost-effective, tissue-saving and aesthetic; they might be used in patients for replacing missing single or multiple anterior or posterior teeth 3,4) . Previous in vitro and in vivo studies are available in literature regarding load-bearing capacities of inlayretained FRC fixed-dental-prosthesis (FDPs) [5][6][7] . A previous study evaluated the effect of pontic materials and occlusal morphologies on the fracture resistance of FRC inlay-retained FDPs and reported that load-bearing capacity values were between 509-598 N 5) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies are available in literature regarding load-bearing capacities of inlayretained FRC fixed-dental-prosthesis (FDPs) [5][6][7] . A previous study evaluated the effect of pontic materials and occlusal morphologies on the fracture resistance of FRC inlay-retained FDPs and reported that load-bearing capacity values were between 509-598 N 5) . In addition, Waki et al investigated the effect of FRC in different positions on the fracture load of inlay-retained FDPs and the values were in the range of 570-943 N 7) .…”
Section: Introductionmentioning
confidence: 99%
“…In other words, conventional inlay cavity and fiber placed near the bottom of the pontic were important in optimizing fiber localization. Özcan et al [ 25 ] evaluated the effect of pontic materials on the fracture resistance of fiber-reinforced composite (FRC) inlay-retained fixed dental prostheses (FDP), reporting that the pontic material did not affect the fracture resistance of FRC FDPs. In the present study, composite resin material was used as a pontic because it is easy to use, has good mechanical properties, and can be used both chair-side and in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the elastic modulus of the supporting core structure has been suggested as a way to increase the fracture resistance of all-ceramic posterior crown restorations 15,16) . Riding on the developments and advancements in the field of fiber-reinforced polymers, the use of fiberreinforced composites (FRC) has increased 17) . Various types of fibers, such as glass fiber, polyester fiber, carbon/ graphite fiber, aramid fiber (kevlar), and ultra-high molecular weight polyethylene fiber (UHMWPE), have been used with composite materials to improve their Fracture resistance of endodontically treated teeth restored with ceramic inlays and different base materials mechanical properties [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Riding on the developments and advancements in the field of fiber-reinforced polymers, the use of fiberreinforced composites (FRC) has increased 17) . Various types of fibers, such as glass fiber, polyester fiber, carbon/ graphite fiber, aramid fiber (kevlar), and ultra-high molecular weight polyethylene fiber (UHMWPE), have been used with composite materials to improve their Fracture resistance of endodontically treated teeth restored with ceramic inlays and different base materials mechanical properties [17][18][19][20][21] . However, there is a need for more information regarding the effects of different base materials on the fracture resistance of endodontically treated teeth restored with ceramic inlays 22) .…”
Section: Introductionmentioning
confidence: 99%